"العلاقات الجزائرية التركية دراسة للفترة 2002-2022م " - بن بوزيد, حكيم (جامعة الوادي university el-oued)
تدور الدراسة حول تقويم العلاقات الجزائرية – التركية في الفترة الواقعة بين سنتي 2002 و2022، باعتبارها مرحلة مهمة في مسار العلاقات الثنائية، حيث تهدف إلى وضع المحددات التي تؤثر في طبيعة العلاقات، وذلك بابراز مختلف مجالات العلاقات الجزائرية – التركية وقضاياها على المستوى الداخلي والاقليمي والدولي. ثم تعرض المعايير التي يمكنها تجسيد التقارب بين البلدين لمواجهة التحديات الراهنة، وتجادل الدراسة أن التغيير في الأفكار، وما يمكن يحققه التقارب من مصالح قد يغير العلاقات الجزائرية – التركية نحو التحالف الإستراتيجي الذي تسعى إليه الدولتان.The study revolves around the evaluation of Algerian-Turkish relations in the period between 2002 and 2022, as an important stage in the course of bilateral relations, intending to establish the determinants that affect the nature of relations, by highlighting the various fields of Algerian-Turkish relations and their issues (Issue Area) On the domestic, regional and international levels. Then it presents the criteria that can embody the rapprochement between the two countries to face the current challenges. The study argues that the change in ideas and what the rapprochement can achieve in terms of interests may change the Algerian Turkish relations towards the strategic alliance that the two countries seek
م.س.ع.22
Keywords: الجزائر، تركيا، العلاقات الدولية، شمال افريقيا.; Algeria, Turkey, International Relations, North Africa.